Post-Surgical TMJ Ankylosis followed by Orthodontic Correction of Class II Div-1 Malocclusion: A Case Report - Hossain, Md Zakir; Ali, Md Sher; Hasan, Md Mahdi; Zakir, Shehreen (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
This case report describe the management of a 17 years old female patient having class II div 1 malocclusion with history of temporomandibular joint surgery. Intraoral examination revealed that patient have proclined maxillary incisors, exaggerated lower curve of spee, and moderate crowding in upper and lower jaw. Other complaints are bite problem, inability to grinding food and unaesthetic smile. After extraction of upper 1st premolars, canine retraction was done which was followed by retraction of severely proclined upper anterior teeth by third order bend in rectangular stainless steel arch wire. For anchorage management TPA, intra oral anchorage with tip back & toe in bends in stainless steel arch wire was satisfactory. Following treatment, marked improvement in patient’s smile, facial profile and lip competence were achieved and there was a remarkable increase in the patient’s confidence and quality of life. Ban J Orthod & Dentofac Orthop, April 2014; Vol-4 (1-2), P.31-34